PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT. BUANA EKACIPTA SARANA TEKNIK JAKARTA - syamsurizal syamsurizal (POLITEKNIK LP3I JAKARTA, 2018)
AbstractThis study aims to determine how much influence of service quality on customer satisfaction at PT. Ekacipta Buana Sarana Teknik Jakarta. Total Respondents in this study were 30 respondents. This study has two variables, the variable quality of service and customer satisfaction. This research uses a quantitative method, data collection technique: observational field research, interviews, questionnaires, and library research. Then, the techniques used linear regression analysis using the test: validity, reliability, kelasik assumption test, normality test,multicollinearity, heteroscedasticity test, autocorrelation test, multiple linear analysis. From the test results showed that Influence the quality of service to satisfaction is satisfaction of 0.83% which means the relationship between service quality and customer satisfaction very strong and positive relationship while consumer satisfaction is equal to 68.89% and the remaining 31.11% is a factor so on others, namely facilities and infrastructure, promotion, delivery of machines from home and abroad, cooperation to achieve joint success that based on kinship.Keywords: Service Quality, Customer Satisfaction